Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Nguyễn Mai Chi

\(\frac{-1}{2}\)x +\(\frac{2}{3}\).(\(\frac{-5}{4}\))=\(\frac{5}{6}\)

Đào Khánh Huyền
11 tháng 7 2016 lúc 12:32

-1/2x+2/3*(-5/4)=5/6

-1/2x+(-5/6)=5/6

-1/2x= 5/6+5/6

-1/2x=5/3

x= 5/3:-1/2

x=-10/3

0o0_ Nguyễn Xuân Sáng _0...
11 tháng 7 2016 lúc 12:42

\(-\frac{1}{2}x +\frac{ 2}{3}\times\left(-\frac{5}{4}\right)=\frac{5}{6}\)


Các câu hỏi tương tự
Trang Đinh Huyền
Xem chi tiết
ImAmNoob!!!
Xem chi tiết
ImAmNoob!!!
Xem chi tiết
Xem chi tiết
nguyen quyet chien
Xem chi tiết
Nguyễn Thị Quỳnh
Xem chi tiết
Nguyen Phan Minh Hieu
Xem chi tiết
boyzzz
Xem chi tiết
Hỏa Long
Xem chi tiết
Phí Quỳnh Anh
Xem chi tiết